S3 The uk's largest severe asthma multidisciplinary team meeting; experience from the first 18 months. (15th November 2016) - Ryan, D; Niven, R; Burhan, H; Corless, J; Diver, S; Fowler, S; Menzies, D; O'Driscoll, R; Scott, S; Sehgal, N; Vyas, A; Allen, D; et al.
Abstract : Background: Severe asthma comprises 5% of all asthma, but over 50% of the asthma healthcare burden. With multi-disciplinary team (MDT) working there is potential to improve patient outcomes and reduce healthcare costs. In 2013 NHS England produced service specifications for severe asthma aiming to develop a limited number of high volume specialist centres. In the North West we have developed a networked approach to specialised severe asthma services; the first Operation Delivery Network for a chronic disease. Representatives from 11 NHS Trusts and a central hub undertake a monthly virtual MDT meeting, with physicians, nurses, physiotherapists, clinical psychologists, speech and language therapists, allergists, pathologists and radiologists represented. All patients being considered for specialised treatments undergo MDT discussion for consensus approval of treatment. Aim: To summarise the experience and case-mix encountered during the first 18 months of operation of our regional virtual severe asthma MDT Methods: We reviewed all cases discussed at the MDT between January 2015 and June 2016. Cases were submitted online via nhs.net accounts, and data entered into a central database managed by two MDT coordinators for MDT discussion. Results: During this period 17 meetings were held, with 208 case-submissions representing 185 patients, mean (SD) 12 (7) discussions per meeting. Indications for case submission included proposals for use of omalizumab, bronchial thermoplasty (BT), and steroid-sparing therapies, and for the discussion of patients with complex clinical issues, often managed across multiple sites. Omalizumab was approved in 81% of cases submitted, and BT in 39%, with more of the latter requiring multiple discussions (30% versus 2%) The most common reasons for non-approval of omalizumab were insufficient steroid requirement, poor adherence, and lack of allergy to a perennial allergen. Thermoplasty was not approved or listed for re-discussion for a variety of reasons, including 10 (43%) that required further investigation. Conclusion: We describe our early experience of a multi-site virtual severe asthma MDT meeting facilitating expert care across a wide geographical area. This ensures governance in the use of novel and expensive severe asthma therapies, strengthens regional collaborations and ultimately aims to provide better patient care.